Imaging Ellipsometry Determination of the Refractive Index Contrast and Dispersion of Channel Waveguides Inscribed by fs‐Laser Induced Ion‐Migration. Issue 19 (25th June 2018) - Moreno‐Zarate, Pedro; Gonzalez, Antonio; Funke, Sebastian; Días, Antonio; Sotillo, Belen; del Hoyo, Jesus; Garcia‐Pardo, Marina; Serna, Rosalia; Fernandez, Paloma; Solis, Javier
Abstract : The measurement of the refractive index of optical waveguides is a difficult task that involves different methods, among which those based on the refracted near field determination (RNF) are likely the ones providing the best resolution. Still, most such methods lack spectral resolution, which impedes accessing the index dispersion of the waveguide, an essential parameter for many applications. In this work, the refractive index of channel waveguides produced by fs‐laser induced ion‐migration in a P2 O5 ‐La2 O3 ‐K2 O‐based glass is measured by imaging ellipsometry. Along with EDX compositional maps and guiding performance, the dispersion and refractive index maps of several waveguides are measured. The results confirm that, in this glass, waveguides are formed due to an enrichment in La in the topmost part of the laser‐excited region which is accompanied by the cross migration of K toward the region underneath. Interestingly, the index contrast of the waveguides shows a wavelength‐independent behavior for wavelengths above ≈600 nm. This indicates that in the compositional range analyzed, La 3+ ions linearly contribute to the glass polarizability due to the relatively large mass of La 3+ ions and the relatively small size of the isolated La‐polyhedra accommodated in the phosphate glass network. Abstract : The work analyzes the spectral dependence of the refractive index of waveguides produced by fs‐laser induced ion‐migration in phosphate glass, using micro‐ellipsometry measurements. The index contrast of the waveguides, formed by La 3+ enrichment in the guiding region, is wavelength independent for λ > ≈600 nm. This is consistent with a linear contribution of the La 3+ ions to the glass polarizability.